1997
DOI: 10.1016/s0887-8994(97)00018-0
|View full text |Cite
|
Sign up to set email alerts
|

Cerebellar mutism in children: Report of six cases and potential mechanisms

Abstract: Cerebellar mutism is a rare finding associated with resection of posterior fossa tumors or cerebellar hemorrhages. We reviewed the medical records of six children, aged 6 to 12 years, who developed cerebellar mutism after resection of a posterior fossa mass or as a result of posterior fossa trauma. From 1989 to 1994, 210 children underwent posterior fossa resection at our institution, and four developed mutism (an incidence of 1.6%). All four patients had primitive neuroectodermal tumors. The fifth patient exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(37 citation statements)
references
References 15 publications
1
33
0
3
Order By: Relevance
“…Indeed, a review of the literature only reveals 9 cases of cerebellar mutism following posterior fossa lesions of vascular origin, including 2 adult cases [3, 4, 6,8,9,10, 41, 42] (table 2). In addition, 3 cases with so-called transient cerebellar mutism following vascular damage to cerebellar and/or adjacent structures of the cerebellum have been described.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, a review of the literature only reveals 9 cases of cerebellar mutism following posterior fossa lesions of vascular origin, including 2 adult cases [3, 4, 6,8,9,10, 41, 42] (table 2). In addition, 3 cases with so-called transient cerebellar mutism following vascular damage to cerebellar and/or adjacent structures of the cerebellum have been described.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Dietze and Mickle [4] did not report any behavioral abnormalities or signs of emotional distress, and Koh et al [6] stated that the mental and cognitive status of their patient was not significantly impaired. Turkel et al [9] investigated 19 children with posterior fossa lesions of which 2 cases had a vascular etiology, focusing on behavioral and emotional disturbances.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…107 Ozimek et al 70 reported 4 cases of CM with bilateral extension of the tumor into the cerebellar hemispheres. There have also been cases of CM with isolated hemispheric lesions such as contusion 51 or metastasis. 85 Neurophysiological studies have shown that the left cerebellar hemisphere is important for the executive functions.…”
Section: Pathophysiologymentioning
confidence: 99%
“…It usually appears as a consequence of posterior fossa surgery in children with cerebellar or fourth ventricle tumors. 52,82,108 Other causes that have been reported are infections, 15,19,24,26,72 posterior fossa hematomas (surgically removed 31,89 or not 60 ), arteriovenous malformations, 33,51,82 a brainstem tumor, 82 a pineal gland tumor, 23 and traumatic cerebellar injury. 15,82 Although this clinical entity is mainly seen in children, there are also reports of CM in adults.…”
mentioning
confidence: 99%